.The position of woman in Nizami’s and Chaucer’s works: Shirin and Criseyde - نیلوفر همت یار; کیان سهیل (تاریخ ادبیات, 2000)
Since one of the options to study the position of women in the national culture of each country is to refer to literary texts, this article compares Khosrow and Shirin by Nezami,to Troilus and Criseyde by Chaucer and by expressing the similarities and differences in them, seeks to recreate the image of women in these two works. Both poets are of great importance in the history of their country's literature. Chaucer, is known as the father of English literature and the Prophet of Love, and Nizami is known as a great author of the sermons and romance stories, to the extent that other authors are influenced by his style. Considering the importance of these two poets, their views on the role of women, particularly in that patriarchal system are considerable. The important thing is the end of the stories. Evidence from the stories shows that Shirin’s Loyalty in love, perseverance and sacrifice make her a role model and a good woman. But by betraying Troilus and joining Diomede, Criseyde becomes a traitorous woman. Nizami fights the dominant culture in his work and has a view on women that is not very much in line with the feudal society of those days; While Chaucer has a sarcastic view. The main similarities of these stories are in the plot, theme and characterization. The earthly love, Shapur and Pendrus as intermediary characters, the death of the male character, Farhad and Diomed who fall in love with female characters, obstacles, separations, disloyalty and advice are to name.